Molecular Structure, Spectroscopy and Photochemistry of Alprazolam - ILDIZ, GÜLCE ÖĞRÜÇ; Tabanez, Andreia M.; Nunes, Antonio; Roque, Jose P. L.; Justino, Licinia L. G.; Ramos, M. Luisa; Fausto, Rui (Elsevier, 2022)
In this article, a comprehensive study of the molecular structure, spectroscopy, and photochemistry of alprazolam (Xanax (R); 8-chloro-1-methyl-6-phenyl-4H-[1,2,4]triazolo[4,3-a][1,4]benzodiazepine) is reported. The structure of the isolated molecule of the compound was investigated using density functional theory (DFT), revealing that the molecule exists in a single conformer, which is associated with 12 equivalent-by symmetry minima. The molecules of the compound were trapped from the gas phase into a low temperature (10 K) argon matrix, and the infrared (IR) spectrum of the matrix-isolated monomers was obtained and assigned. The matrix-isolated molecules were then subjected to in situ ultraviolet (UV) irradiation . It was concluded that alprazolam is photostable under these experimental conditions, contrarily to what is known to happen for the compound in solution or in solid state in the presence of excipients used in the pharmaceutical formulations. An explanation for the photostability of the matrix-isolated compound is provided, based on rapid recombinations of the biradical formed from the UV-induced diazepine ring cleavage or the chlorine atom and the complementary radical resulting from the scissoring of the C-Cl bond, which are favored by the cage confinement of the matrix-isolated molecules. The major fragmentation channels of the alprazolam molecule upon electron bombardment (70 eV) were determined by analysis of its electron ionization mass spectrum, which reveals that the major primary fragmentation processes lead to formation of cyanobenzene, N-2 , HCl (Cl-2), and benzene. The compound was also investigated in solution by multinuclear (H-1, C-13 and N-15) nuclear magnetic resonance (NMR) and ultraviolet (UV) spectroscopies, and in crystalline phase (P-1 polymorph) through IR and Raman spectroscopies. In addition, the structure of the crystal, previously reported in the literature [M. R. Caira, B. Easter, S. Honiball, A. Horne and L. R. Nassimbeni, Structure and Thermal Stability of Alprazolam and Selected Solvates, J. Pharm. Sci., 1995 , 84 , 1379-1384], was revisited in order to evaluate the relative importance of the different types of intermolecular interactions , using Hirshfeld surface analysis, the CE-B3LYP energy decomposition model, and the harmonic oscillator model of aromaticity (HOMA) index. Finally, the enthalpy of sublimation of the crystal was estimated from the CE-B3LYP calculated lattice energy.
Keywords: Alprazolam; Molecular Structure; Spectroscopy; Unimolecular Photochemistry; Fragmentation Channels; Intermolecular Interactions